Fixed Shading Scenarios to Optimize Lighting Performance and Energy Efficiency in Office Buildings Case Study of Dubai Design District - Hamad, Khadije (2021)
As the global movement is moving towards reducing the leading causes of global warming, the United Arab Emirates is one of the striving countries that is moving towards tackling this phenomenon by launching initiatives that help reduce and control these emissions. In the UAE, the building’s cooling loads account for 60% of the electricity load during the summer in Dubai. Therefore, buildings need a profound and practical solution to reduce the energy consumption caused by the building facades. As the primary façade materials used in Dubai are fully glazed facades, this paper aims to illustrate the potential reduction in energy consumption and daylight for a fully glazed building in the Dubai Design District. Although this case study already includes a shading device, the aesthetic importance for architects impacted the real benefits of the fixed shading device on this building. Therefore, the study aims to quantify the absolute energy consumption reduction caused by applying different, more beneficial shading designs for that particular building. An office building was selected as the case study for this paper in Dubai Design District, specifically building six. An extensive literature review was performed in this paper to highlight relevant information to incorporate into the research methodology and simulation strategy. The existing building was modeled on the simulation tool IES VE Software and was used as the base case scenario. Six different fixed shading devices were simulated and texted on the building against the base case. These scenarios were in this order: Overhang Louvers in three dimensions 1200mm, 1500mm and 1800mm, 90 Vertical Fins, 45 Vertical fins as scenario two, Egg-crate, Horizontal Louvers, Vertical Louvers and a double skin façade in scenario six. The energy consumption test was carried on every month of a year with a total energy consumption result for each scenario. The daylight analysis was conducted on one typical office space during three timings, 9:00 am, 12:30, and 17:00, on two dates, 21st of December and 21st of June, to check variations. The results proved that fixed shading devices on a fully glazed office improved energy consumption by using all the scenarios. Therefore, it is always beneficial to use external shading devices. The results in chapter 5 show that the Egg-crate scheme performed most effectively on the office building case study achieving a reduction in energy consumption of 8.2% from the base case result in a year. Also, in Daylighting analysis, the most effective was the egg-crate scenario, where it achieves a reduction in average illuminance level of 60% in both December and June. The second-best method was the Horizontal Louvers, where it achieved a reduction in energy consumption by 7.7% compared to the base case, and in daylight, it achieved a decrease of 50% in Both selected months. Horizontal louvers were generally more effective than vertical louvers. Although this study tests the vertical louvers in two degrees yet the horizontal proves to be more effective. The annual energy consumption of the optimal scenario is reduced from 1670 MWh to 1532MWh in the Egg-crate scenario three, which is a high reduction of 138MWh per year. Moreover, daylighting analysis shows decreased average illuminance levels from 407.8 to 154.97 Lux, equivalent to a 60% reduction in December and June. The results show that external fixed shading devices on the office building façade reduce energy consumption dramatically, increasing building efficiency and performance. It is recommended that external shading devices be applied at the early stages of design phases, especially in fully glazed building facades that are very common in office buildings in Dubai. It is also essential to consider that shading device calculations should be done according to the latitudes and longitude of the city of the case study, in this case, Dubai city, to get the optimum energy-saving results possible.